Relationship between Family Mobility and the Incidence of Dengue Hemorrhagic Fever at Sleman Regency, Yogyakarta, Indonesia - Tri Wulandari Kesetyaningsih; Dimas Pradana Putra; Farizki Muhammad Muhammad (Fakultas Kedokteran Universitas Lambung Mangkurat, 2019)
Abstract: Dengue hemorrhagic fever is a public health problem in the world. Transmission of dengue through Aedes mosquito, so that the incidence is locally limited to the distance of flying. A role of mobility towards dengue spreading have not been consistent. This study aims to provide information about the role of family members’ mobility in dengue incidence by using observational study with case control design. Case group are families whose members have suffered from dengue in 2014-2016 and control groups are their neighbors. There were 114 people for case and 116 for control group which is divided into two locations namely Sleman and gamping. Data on DHF patients and their addresses were obtained from Health Office, and mobility obtained through questionnaires then analyzed using chi square to determine the role of mobility in DHF incidence. The results show that there is no significance relationship between family mobility and the incidence of DHF. In Gamping, P high - low is 0.307 and P moderate - low is 0.523. In Sleman, P high - low is 0.685 and P moderate - low is 0.438. It was concluded that the mobility of family members was not a risk factor for dengue infection. Keywords: family mobility, DHF incidence, risk factor